Decomposition of nitrous oxide in hydrated cobalt(i) clusters: a theoretical insight into the mechanistic roles of ligand-binding modes. Issue 31 (29th July 2021) - Demissie, Ephrem G.; Lam, Wing Ka; Thompson, Hayden; Tang, Wai Kit; Siu, Chi-Kit
Abstract : In small [Co(N2 O)(H2 O) n ] + clusters, N2 O can bind to Co + through its O-end or N-end and then be decomposed into [CoO] + + N2 or [CoOH] + + N2 + OH, respectively. However, in large clusters, the decomposition is effective only through the N-bound mode. Abstract : Hydrated cobalt(i ) cluster ions, [Co(H2 O) n ] +, can decompose the inert nitrous oxide molecule, N2 O. Density functional theory suggests that N2 O can anchor to Co + of [Co(N2 O)(H2 O) n ] + through either O end-on (η 1 -OL) or N end-on (η 1 -NL) coordinate mode. The latter is thermodynamically more favorable resulting from a subtle π backdonation from Co + to N2 O. N2 O decomposition involves two major processes: (1) redox reaction and (2) N–O bond dissociation. The initial activation of N2 O through an electron transfer from Co + to N2 O yields anionic N2 O −, which binds to the metal center of [Co 2+ (N2 O − )(H2 O) n ] also through either O end-on (η 1 -O) or N end-on (η 1 -N) mode and is stabilized by water molecules through hydrogen bonding. From η 1 -O, subsequent N–O bond dissociation to liberate N2, producing [CoO(H2 O) n ] +, is straightforward via a mechanism that is commonplace for typical metal-catalyzed N2 O decompositions. Unexpectedly, the N–O bond dissociation directly from η 1 -N is also possible and eliminates both N2 and OH, explaining the formation of [CoOH(H2 O) n ] + as observed in a previous experimental study. Interestingly, formation of [CoO(H2 O) n ] + is kinetically controlled by the initial redox process between Co + and the O-bound N2 O, the activation barriers of which in large water clusters ( n ≥ 14) are higher than that of the unexpected N–O bond dissociation from the N-bound structure forming [CoOH(H2 O) n ] + . This theoretical discovery implies that in the present of water molecules, the metal-catalyzed N2 O decomposition starting from an O-bound metal complex is not mandatory.